ASSIGNMENT: SERVICE LEARNING - Rittle, Marc (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
As students in a Social Problems course, you will be expected to complete one to three hours of volunteer work in the community, this being a practical application to what you learn in the classroom. Within the first five weeks of the semester, you will select your field site (see attached list) and arrange your own appointment with the organization. This is a one-time assignment, and you are responsible for coordinating your own schedule.